Understanding value creation in cultural industries: strategies for creating and managing meaning. Issue 3 (18th June 2020) - Yin, Eden; Phillips, Nelson
Abstract : Purpose: This paper aims to analyse the valuation of cultural products and explores what this process means for organizations involved in their production and marketing. Design/methodology/approach: The authors develop the arguments using a number of mini-cases and industry examples. Findings: The main thesis is that the meaningfulness and value ambiguity of cultural products shift the focus of valuation away from the products themselves towards how certain agents in the socio-cultural environment identify and certify these products. This paper discuss how valuation takes place via selection systems and how the nature of cultural products drives the dominance of one selection system over others. Research limitations/implications: Theories on value creation needs to take consideration of the critical role played by the selection system instead of just the firms that produce these products. Practical implications: Organizations engaged in producing highly symbolic products need to manage selection systems and related industry dynamics to establish an enduring competitive advantage. Social implications: Value creation is a collective social efforts. Every member of the society can play a central role in this process. Better engaging various member of the society to enable them actively participate in the value creation process is what organizations today need to consider, instead of just treating individuals in the society as a "customer" who only passively consume. This research calls for the true empowerment of every member of the society to facilitate collective creativity and participation in the value creation endeavour that benefits the entire society as a whole. Originality/value: It is the first paper that has created a conceptual link between the type of selection system and product categories. In other words, it takes existing literature on value creation and selection system one step further by creating the alignment or match between types of selection system and types of product categories. Therefore, it offers academics and practitioners a much detailed understanding on how value creation is conducted across different product categories.